Evolusi Konsep Keamanan Energi - Ramadhani, Arshie (UI Scholars Hub, 2017)
Energy security concept is contextual and understood in different ways in different context. This paper examines the development of the literatures of energy security. Using chronological method of organization, this paper classifies the literatures into three different periods: 1970-1990, 2000-2010, and post-2010. From this classification, it is found that there is a proliferation of themes in the definition of energy security concept. The concept has expanded from what was initially limited to availability and affordable price, to include themes such as infrastructures, environment, social impacts, efficiency, governance and public policy. This raises a debate as to whether the energy security concept need to be broadened to accomodate the emergence of new challenges or to remain limited in definition so that it would not lose its meaning. This paper then further argues that the definition of energy security should be attached to the definition of security as, “survival in the face of existential threat,” so that security concept itself would be able to retain its focus. Taking a contextual perspective and conceptual variation over time, this paper aims to present a theoretical debate on how energy is understood as a security issue and to serve as a reference for energy policy making.